Clinician's attitude to enteral nutrition with percutaneous endoscopic gastrostomy: a survey in China - Yijie Zhang; Chen Ma; Chenxi Li; Qian Chen; Meifen Shen; Yuyu Wang (BMC, 2021)
Abstract Background Percutaneous endoscopic gastrostomy (PEG) is recommended for long-term enteral nutrition. However, long-term nasogastric (NGT) feeding is still commonplace in China. We surveyed Chinese clinicians' opinions toward PEG feeding in order to identify the potential barriers to acceptancy of PEG feeding. Methods A self-reported questionnaire was developed and distributed to 600 doctors. Five-point Likert scales were used for most responses. Results Of 525 respondents, the mainly nutritional support method was NGT while PEG was less used. Doctors working in the tertiary class A hospitals and radiotherapy department were more likely to choose PEG feeding (p = 0.000). Overall, 241 (46%) participants did not know PEG and 284 (54%) have different understanding degree of PEG. Age (p = 0.002), working life (p = 0.044) and professionalism (p = 0.005) were significantly related to the understanding of PEG. Levels of agreement was high (score of 3.47) for using PEG in patients with prolonged stroke-associated dysphagia. There was high agreement level in the statement that PEG was unnecessary when NGT could sustain the basic needs of patients, though better outcome can be predicted with PEG feeding. The highest scoring factor (score of 3.91) that influenced clinicians' choice of PEG was resistance from patients and families and the second one was the poor cooperation among departments (score of 3.80). Conclusions Doctors' insufficient knowledge of PEG feeding, resistance from patients and families, poor cooperation among departments, all these factors leading physicians to prefer more conservative treatment to avoid disputes rather than better ones.